Hindī ke cāra gadya-kavi aura unakā kāvya - Kāka, Tejanārāyaṇa, 1914- (Tirupati Prakāśana, 1983)
Critical study of the works of Hindi prose writers with poetic excellence, Rāya Krshṇadāsa, b. 1892, Viyogī Hari, b. 1896, Acharya Caturasena, 1891-1960, and Vrndāvanalāla Varmā, 1890-1969.